2020
DOI: 10.3390/agronomy10020167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca(NO3)2 Stress on Mitochondria and Nitrogen Metabolism in Roots of Cucumber Seedlings

Abstract: Cucumber is a major vegetable crop grown in facilities, and its seedlings are sensitive to salinity. Thus, it is important for cucumber cultivation to research the effects of Ca(NO3)2. In this study, we investigated salt-sensitive Chunqiu (CQ) and salt-tolerant BoMei 49 (BM) seedlings, the changes to the enzymes involved in the mitochondria antioxidant system in the seedlings, and the changes in the MPTP (Mitochondrial Permeability Transition Pore) opening, mitochondrial membrane fluidity, mitochondrial membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…A result of rising sea levels and the expansion of arid regions brought on by global warming, the amount of salinized soil is expanding substantially and has become one of the major issues restricting agricultural production [6,7]. Excessive application of solely chemical fertilizer can aggravate salt stress, especially under the conditions of large evaporation of Horticulturae 2023, 9, 1015 2 of 21 soil water in protected cultivation [8,9]. Using organic manure is a practical way to ensure yield and improve the quality of crops, especially in saline soils [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A result of rising sea levels and the expansion of arid regions brought on by global warming, the amount of salinized soil is expanding substantially and has become one of the major issues restricting agricultural production [6,7]. Excessive application of solely chemical fertilizer can aggravate salt stress, especially under the conditions of large evaporation of Horticulturae 2023, 9, 1015 2 of 21 soil water in protected cultivation [8,9]. Using organic manure is a practical way to ensure yield and improve the quality of crops, especially in saline soils [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The overproduction of ROS and subsequent oxidative damage commonly occur under salt stress ( Alexander et al, 2020 ; Yang et al, 2020 ). Proteomics analysis showed that Ca(NO 3 ) 2 stress affected the accumulation of proteins involved in stress responses and antioxidant defense, and exogenous BR increased the accumulation of antioxidant enzymes and proteins involved in the responses to osmotic stress in tomatoes under Ca(NO 3 ) 2 stress ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…The excessive Ca(NO 3 ) 2 content in the soil could cause serious damage to both the yield and quality of vegetables. The superfluous Ca(NO 3 ) 2 accumulated in vegetables may lead to oxidative damage and metabolic disturbances, which finally results in crop failure in Chinese cabbage, cucumber and tomato [2,5,6]. Several studies have indicated that vegetables contribute to the main source of nitrate in humans.…”
Section: Introductionmentioning
confidence: 99%